The dsDNA, Anti-dsDNA Antibody, and Lupus Nephritis: What We Agree on, What Must Be Done, and What the Best Strategy Forward Could Be - Rekvig, Ole Petter (Frontiers in Immunology, 2019)
This study aims to understand what lupus nephritis is, its origin, clinical context, and its pathogenesis. Truly, we encounter many conceptual and immanent tribulations in our attempts to search for the pathogenesis of this disease – and how to explain its assumed link to SLE. Central in the present landscape stay a short history of the early studies that substantiated the structures of isolated or chromatin-assembled mammalian dsDNA, and its assumed, highly controversial role in induction of anti-dsDNA antibodies. Arguments discussed here may provoke the view that anti-dsDNA antibodies are not what we think they are, as they may be antibodies operational in quite different biological contexts, although they bind dsDNA by chance. This may not mean that these antibodies are not pathogenic but they do not inform how they are so. These strange contradictions linked to a dsDNA-binding IgG is founded by data and inconclusively accepted hypothesis and algorithms. Thus, we have not reached clear definitions to describe origin and impact of anti-dsDNA antibodies, SLE, or lupus nephritis. This theoretical study centers the content around the origin and impact of extra-cellular DNA, and if dsDNA has an effect on the adaptive immune system. The pathogenic potential of chromatin-anti-dsDNA antibody interactions is limited to incite lupus nephritis and dermatitis which may be linked in a common pathogenic process. These are major criteria in SLE classification systems but are not shared with other defined manifestations in SLE, which may mean that they are their own disease entities, and not integrated in SLE. We miss an organized approach to prioritize a comprehensive perspective by not taking all aspects of the syndrome SLE into account. This can only be achieved by concentrating on the interactions between its different elements. System science provides a framework in which assessment of data generated by experts in different fields can be combined and confronted with each other in order to determine what we agree on, what must be done, and what the best strategy forward must be. This has not been done yet in a systematic context.